Diagnosis and prognosis of a disease using "neerkuri & neikuri" urinary examination method in siddha medicine: a literature study - Dharshini, K.V. (Proceedings of 2 International Conference on Ayurveda, Unani, Siddha & Traditional Medicine 2014, 2014)
Siddha system has unique methods in disease diagnosis and mainly based on the method En- vagaithervu. Among the Envagaithervu, Neerkuri and neikuri is a remarkable diagnostic tool and well explained by Sage Theriyar. However, the methods have not been in routine use in Sri Lanka. As these methods are ancient wisdom the study aimed to done a literature survey on these methods. Systemic review has done using the siddha medicine books and research articles. The Neerkuri assessment has been done using the colour, weighing measure, odour, froth & decrease in volume of the urine. For example, urine in Saffron colourindicates high temperature of the body andGreenish black indicates respiratory illnesses. Neikuri assessment is based on the na- ture of spread. direction of spread and shapes formed by the oil drop in the urine. If the oil drop is snake in shape that indicates vatha diseases and if the oil drop spreads fast or becomes small like mustard or gets mixed completely with urine or sinks in urine that indicates a bad prognosis. Studies have indicated almost all type of disease identifications using the Neerkuri and Neikury methods. The neerkuri and neykuri methods are convenient, reliable and cost effective methods to diagnosis and prognosis of a disease. Validation of these methods may have impact on public health prospective.
Keywords: Neerkuri; Neikuri; Urinary examination